2015
DOI: 10.1007/s11095-015-1797-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell-Mediated Immunity to Suppress High Fat Diet-Induced Obesity and Insulin Resistance

Abstract: Purpose To assess the effect of immune modulators on high fat diet-induced obesity and insulin resistance. Methods C57BL/6 mice were fed a high fat diet and injected intraperitoneally with cyclosporine A, fingolimod, or vehicle twice weekly for 15 weeks. Body weight and food intake were manually measured every other day. Glucose tolerance test, insulin sensitivity, and body composition were examined and compared between the control and the immune modulator treated animals. Tissue samples were collected at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Instead, suppressing viperin expression improved glucose homeostasis in HFD-fed mice. This is in line with earlier findings showing that suppressing innate antiviral immunity using cyclosporine A protects against HFD-induced obesity and insulin resistance in mice [ 40 , 41 ]. Recent data revealed that insulin receptor tyrosine kinase substrate (IRTKS) mediates suppression of antiviral responses.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, suppressing viperin expression improved glucose homeostasis in HFD-fed mice. This is in line with earlier findings showing that suppressing innate antiviral immunity using cyclosporine A protects against HFD-induced obesity and insulin resistance in mice [ 40 , 41 ]. Recent data revealed that insulin receptor tyrosine kinase substrate (IRTKS) mediates suppression of antiviral responses.…”
Section: Discussionsupporting
confidence: 93%
“…Data from several studies suggest that T-cell activation might be linked to weight gain. It was shown that treatment of mice on an obesogenic diet with anti-CD40L antibody (blocks costimulation needed for T-cell activation), cyclosporine A (interferes with activity and growth of T cells), or fingolimod (inhibits T-cell emigration from lymphoid organs) leads to decreased weight gain (14,15). This was accompanied by decreased liver weight/ steatosis, decreased (CD11c + ) macrophage infiltration of WAT, and improved insulin sensitivity, all phenotypes that we also observed in our Tg T-PPAR-b mice.…”
Section: Discussionmentioning
confidence: 99%
“…Improved insulin sensitivity in response to CsA has been reported recently in obese high-fat-fed C57Bl/6 mice. 26 However, caution must be exercised in applying these findings to clinical studies as immunosuppressive drugs such as CsA increase the risk of developing diabetes mellitus, most likely via effects on insulin secretion. 27 Analysis of individual lipid species in VLDL and IDL/ LDL fractions indicated that although absolute levels of lipid species in plasma were increased, lipid composition per particle (per phosphatidylcholine or apoB) did not change for the vast majority of lipid species.…”
Section: Discussionmentioning
confidence: 99%